Diversity and abundance of bees (Hymenoptera: Apidae) in the campus 4 of Ahmad Dahlan University - Ichsan Luqmana Indra Putra; Haris Setiawan; Suci Resty Rahmadini (Jurnal Pijar Mipa, 2022)
Land conversion around campus 4 of Ahmad Dahlan University Yogyakarta affects the diversity and abundance of pollinating insects, one of which is bees. The purpose of this study was to calculate the level of diversity and abundance of bees on campus 4 UAD and its surroundings. The sampling area consisted of 4 plots, with each plot measuring 1750 m2( 35 m x 50 m) determined using the observation method. Sampling was carried out three times, which was carried out in the morning at 07.00 – 11.00 and continued in the afternoon at 15.00 – 17.00. Bees were identified by comparing their morphological characters with identification reference books and journals. The Spearman correlation test then analyzed the bee abundance data and abiotic factors. The results showed that the level of bee diversity on campus 4 UAD and its surroundings was moderate (1 H' 3). The most abundant bee species was Xylocopa aestuan, with 118 individuals, and the least abundant was Apis mellifera, with 7 individuals. The conclusion of this study is the state of the ecosystem on campus 4 UAD and its surroundings, there is a disturbance in the form of land use change, but bees can still tolerate the disturbance.